Reference intervals of biochemical parameters in Chilean adults. - Letelier, Pablo; Acuña, Rodban; Garrido, Ignacio; López, Jorge; Sanhueza, Guillermo; Seguel, Caren; Guzmán, Neftalí; Hernández, Alfonso (Journal of Medical Biochemistry, 2023)
Background. Establishing reference intervals (RIs) in clinical laboratories is essential, as these can vary due to inter-individual variability as well as the analytical methods used. The purpose of this study was to determine RIs for various biochemical markers in the Chilean adult population. Methods. A sample of 1,143 individuals was selected from the UC Temuco Clinical Laboratory database, which were analysed by sex. The Tukey Fence method was used to detect outliers and the RIss were established using the non-parametric method recommended by the IFCC. Results. The RIs obtained for the female sex were: Urea 14.9-44.2 mg/dL, AST 11.8-41.4 U/L, ALT 7.9-67.2 U/L, Alkaline Phosphatase 50-150 U/L, Total Bilirubin 0.206-1.017 mg/dL, Direct Bilirubin 0.088-0.287 mg/dL, Uric Acid 2.5-6.1 mg/dl and Total Proteins 6.63-8.03 g/L and for males: Urea 19.7-49.1 mg/dL, AST 13.2-48.2 U/L, ALT 11-114.3 U/L, Alkaline Phosphatase 56-140 U/L, Total Bilirubin 0.268-1.408 mg/dL, Direct Bilirubin 0.109-0.439 mg/dL, Uric Acid 3.4-7.7 mg/dL and Total Proteins 6.63-8.03 g/L. Conclusions. A panel of RIs for locally-relevant biochemical parameters has been established. When comparing these results with other studies and those reported by reagent manufacturers, some differences were observed. This study thus contributes to increase the reliability in the interpretation of laboratory results and therefore to the clinical management of patients.
Keywords: References intervals, Biochemical markers, Interindividual variability.